Effects of Exogennous Ebr on Physiological And Biochemical Characteristics of Soybean Under Cadmium Stress (Bangladesh Journal of Botany, 2024)
Cadmium (Cd) is one of the highly toxic, non-essential heavy metals that inhibit plant growth and development. The differences in physiological indicators and leaf microstructure between cadmium-tolerant and cadmium-sensitive soybean under Cd stress were studied. The results showed that the photosynthetic efficiency of cadmium-sensitive soybeans was higher after cadmium stress so as to maintain the normal growth of the plants. Compared with that of cadmium-tolerant soybeans, the photosynthetic rate of cadmium-sensitive soybeans under cadmium stress had a higher correlation with each physiological indicator. Overall, EBR affected cadmium-tolerant soybean under cadmium stress mainly by changing the leaf cell structure and maintaining the integrity of cell structure, thereby increasing the net photosynthetic rate of soybean leaves, ultimately maintaining the normal growth of plants.Bangladesh J. Bot. 53(2): 327-335, 2024 (June)